Bichronous scientific writing course for medical faculty during Covid-19: a SWOT analysis experience - Khojasteh, Laleh; Zarifsanaiey, Nahid; Karimian, Zahra (Frontiers in Education, 2024)
Introduction Writing and publishing scholarly articles in international peer-reviewed journals can be a challenging undertaking for medical and healthcare professionals in universities, especially in non-English speaking countries. Surprisingly, very few faculty members report receiving guidance on scientific writing. To encourage more faculty engagement in professional development courses aimed at enhancing their writing abilities, we have revamped scientific writing courses to incorporate bichronous (a combination of asynchronous and synchronous) teaching methods. Methods After forming a team, we performed a SWOT (strengths, weaknesses, opportunities, and threats) study of the medical faculty’s present programs and proposed alternatives to prior course issues. In this interventional study, fifty-nine eligible medical educators selected by purposeful sampling underwent a two-and-a-half-month bichronous scientific writing course from March to August 2021. The perspectives of the participants were evaluated through a SWOT analysis. The data were collected through online semi-structured interviews, and data collection continued until data saturation was achieved (40 participants). Data were then coded and analyzed based on conventional qualitative content analysis principles. Results Our planned blending sequence and e-feedback increased the medical faculty’s drive to learn, self-confidence, and autonomy while improving their writing skills. Poor ICT and network infrastructure hindered course adoption. Due to the course’s time and the faculty’s own online teaching, many battled with computer vision syndrome, self-discipline, and distractions. Our participants struggled with self-discipline and distractions, so setting a daily time limit may help them concentrate. Discussion Given the faculty’s demanding professional lives, this designed course provided a learning opportunity for many that would not have been feasible otherwise.